Invasive candidiasis among high prevalence neurological patients - Rinawati, Weny; Kumalawati, July; Bardosono, Saptawati; Immanuel, Suzanna; Sukartini, Ninik; Indrasari, Nuri Dyah (The Journal of Infection in Developing Countries, 2022)
Introduction: Invasive candidiasis is a severe form of infection. The incidence of invasive fungal infections has increased, due to the increasing number of patients with impaired immunity who are being treated through prolonged stay in hospital facilities. Neurological patient treatment methods such as antimicrobials, corticosteroid, central venous catheter (CVC), total parenteral nutrition, and mechanical ventilation use are associated with common risk factors for invasive candidiasis. Our study demonstrated invasive candidiasis prevalence among neurological patients. Methodology: A cross-sectional study was done with consecutive sampling of neurological patients who were hospitalized from January 2017 to February 2020 at the Mahar Mardjono National Brain Center Hospital East Jakarta Indonesia. Patients with sepsis, septic shock, or fever (> 38.5 °C), and who had not received antifungals before culture were enrolled in the study. Clinical specimens were obtained from blood, liquor cerebrospinal or other sterile sites, CVC, respiratory tract specimens, and urine or other non-sterile sites. Socio-demographic data, potential risk factors based on previous studies, clinical, and other tests data were obtained from medical records. Classification of invasive candidiasis was according to the Paphitou classification criteria. Results: One hundred and two subjects met the study criteria. The prevalence of invasive candidiasis in neurological patients was 13.7%. All of the isolates were C. parapsilosis. Conclusions: The prevalence of invasive candidiasis was high in the samples studied. The infection was associated with septic shock, tracheostomy, and duration of use of central venous catheter, ventilator, and steroids.